UJI PENURUNAN KADAR GLUKOSA DARAH OLEH EKSTRAK ETANOL 70% DAUN BUNCIS (Phaseolus vulgaris L) PADA KELINCI JANTAN YANG DIBEBANI GLUKOSA - Desy Kurniawati; EM Sutrisna; Arifah Sri Wahyuni (Universitas Muhamadiyah Surakarta, 2012)
This research aim to know the descent of blood glucose rate by extract etanol 70% of bean leaf at male rabbit which induced glucose. Research using the method test glucose tolerance of oral was including category research of sham eksperimental with complete random attempt device of unidirectional pattern. This research use 20 male rabbits which divided in 5 treatment group. Group I given by CMC Na 1% as negative control, group II given by acarbose suspensi 2,33 mg/kgBB as positive control, group III, IV and V given by extract etanol 70% bean leaf with each dose 200, 300 and 450 mg/kgBB. Treatment given at once after test animal induced glucose 50% ( 5 ml/1,5 kgBB). Glucose blood rate to define every 30 minute, 0 minute until 300 minutes by using method of enzimatik GOD PAP (Glucose Oxidase Phenol Aminoantipyrina Peroxidase), what was later then analysed with one track Anava and continued by test of LSD (Least Significant Diffeerence) with trust level 95%. Extract etanol 70% bean leaf with dose 200, 300 and 450 mg/kgBB have effect descent of blood glucose rate to negative control of CMC Na 1% (p = 0,000) with each percentage descent of blood glucose rate (% PKGD) 80,88 ± 0,93 ; 82,73 ± 0,67 and 85,32 ± 0,21.Keyword : Extract etanol 70%, bean leaf (Phaseolus vulgaris L), degradation of glucose rate